2009
DOI: 10.1002/hbm.20814
|View full text |Cite
|
Sign up to set email alerts
|

Mapping brain abnormalities in boys with autism

Abstract: Children with autism spectrum disorder (ASD) exhibit characteristic cognitive and behavioral differences, but no systematic pattern of neuroanatomical differences has been consistently found. Recent neurodevelopmental models posit an abnormal early surge in subcortical white matter growth in at least some autistic children, perhaps normalizing by adulthood, but other studies report subcortical white matter deficits. To investigate the profile of these alterations in 3D, we mapped brain volumetric differences u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 83 publications
5
48
0
1
Order By: Relevance
“…Similarly, DTI supports these MRI findings by showing a reduced integrity of WM tracts that are part of these 'social' fronto-temporal cortical and subcortical networks Barnea-Goraly et al 2004;BarneaGoraly et al 2010;Ben Bashat et al 2007;Bloemen et al 2010;Brito et al 2009;Brun et al 2009;Catani et al 2008;Conturo et al 2008;Cheng et al 2010;Cheung et al 2009;Groen et al 2011;Jou et al 2011;Ke et al 2009;Keller et al 2007;Knaus et al 2010;Lange et al 2010;Lee et al 2007a;Noriuchi et al 2010;Pardini et al 2009;Pugliese et al 2009;Sahyoun et al 2010;Shukla et al 2010aShukla et al , 2011Sivaswamy et al 2010;Sundaram et al 2008;Thakkar et al 2008;Weinstein et al 2011). See Fig.…”
Section: Social Cognition and Interaction Deficitsmentioning
confidence: 65%
“…Similarly, DTI supports these MRI findings by showing a reduced integrity of WM tracts that are part of these 'social' fronto-temporal cortical and subcortical networks Barnea-Goraly et al 2004;BarneaGoraly et al 2010;Ben Bashat et al 2007;Bloemen et al 2010;Brito et al 2009;Brun et al 2009;Catani et al 2008;Conturo et al 2008;Cheng et al 2010;Cheung et al 2009;Groen et al 2011;Jou et al 2011;Ke et al 2009;Keller et al 2007;Knaus et al 2010;Lange et al 2010;Lee et al 2007a;Noriuchi et al 2010;Pardini et al 2009;Pugliese et al 2009;Sahyoun et al 2010;Shukla et al 2010aShukla et al , 2011Sivaswamy et al 2010;Sundaram et al 2008;Thakkar et al 2008;Weinstein et al 2011). See Fig.…”
Section: Social Cognition and Interaction Deficitsmentioning
confidence: 65%
“…On the other hand, Brun et al (2009) found significantly decreased cortical volumes in the parietal, left temporal, and left occipital lobes, bilaterally, using TBM. Alterations of the basal ganglia, especially the caudate nuclei, have been repeatedly described in ASD patients and were often found to correlate with impaired motor performance or repetitive and stereotyped behavior (for review see (Nickl-Jockschat et al 2012)).…”
Section: Voxel-based and Tensor-based Morphometrymentioning
confidence: 88%
“…Brun et al [46] suggested that delayed or aberrant myelination is a cause of abnormal white matter in autism. The development of myelin sheaths allows a smooth flow of neural impulses through the brain [47].…”
Section: Discussionmentioning
confidence: 99%